Beban Kognitif Siswa Dalam Pembelajaran Matematika Berorientasi Pada Higher Order Thinking Skills (HOTS) - Riya Dwi Puspa; Abdur Rahman As'ari; Sukoriyanto Sukoriyanto (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: This research is research that have purpose to describe students' cognitive loads in mathematic learning oriented to Higher Order Thinking Skills (HOTS). Research method that is used in this research is descriptive qualitative. The results showed that the intrinsic cognitive loads were caused by students'  difficulties in finding concept of integral, students' difficulties in doing operation of  algebraic form, students' difficulties in solving HOTS problems at level of analyzing, evaluating and creating. Extraneous cognitive loads were caused by using local language that is used by teacher for giving information, time alocation for doing discussion was too short, noise during the discussion and teacher give explanation fastly. Germane cognitive loads were caused by the use of technology in learning such as PowerPoint slides, Google for Education and the internet for accessing to online learning resources, and the existence of asking questions that stimulate students' HOTS and group discussion. Abstrak: Penelitian ini merupakan penelitian yang bertujuan untuk mendeskripsikan beban kognitif siswa dalam pembelajaran matematika yang berorientasi pada Higher Order Thinking Skills (HOTS). Metode penelitian yang digunakan dalam penelitian ini adalah kualitatif deskriptif.  Hasil penelitian menunjukkan bahwa beban kognitif intrinsik disebabkan oleh kesulitan siswa dalam menemukan konsep integral, kesulitan siswa dalam melakukan operasi bentuk aljabar, kesulitan siswa dalam menyelesaikan soal HOTS pada level menganalisis, mengevaluasi, dan mengkreasi. Beban kognitif extraneous disebabkan oleh penggunaan bahasa daerah yang digunakan guru dalam menyampaikan informasi, alokasi waktu untuk berdiskusi yang cukup singkat, kegaduhan saat diskusi berlangsung, dan guru memberikan penjelasan dengan cepat. Beban kognitif germane disebabkan penggunaan teknologi dalam pembelajaran, misalnya slide powerpoint, Google for Education dan internet untuk akses sumber belajar online, serta adanya pengajuan pertanyaan yang menstimulasi HOTS siswa dan diskusi kelompok.